Races of Puccinia graminis on barley, oat, and wheat in Canada from 2015 to 2019. Issue 3 (4th May 2021) - Fetch, T.; Mitchell Fetch, J.; Zegeye, T.; Xue, A.
Abstract: Stem rust is a major disease on barley, oat, and wheat crops worldwide. The primary means of control is by host resistance genes that are incorporated into commercial varieties and have been effective against most races of Puccinia graminis Pers., the causal pathogen. Since this pathogen continually mutates, analyzing the population virulence structure is crucial to detect new races with increased virulence. Stem rust samples were collected from 2015 to 2019 from the Canadian provinces of Manitoba, Ontario, Quebec, and Saskatchewan to find the prevalence of stem rust in barley ( Hordeum vulgare L.), oat ( Avena sativa L.), and wheat ( Triticum aestivum L.) fields and the virulence dynamics in the two pathogen populations. Stem rust was absent in cultivated wheat and at trace (<1%) levels of incidence in barley and oat fields in all years. While the dominant races of P. graminis f. sp. tritici were MCCDC (54.5%) and TPMKC (27.3%) in 2015, and TMRTF (29.2%) in 2016, race QFCSC was dominant in 2017 (52.0%), 2018 (88.4%), and 2019 (81.3%). The dominant race of P. graminis f. sp. avenae was TJS from 2015 to 2018. Race TJS declined in frequency across the years, from 89.5% (2015) to 73.7% (2016), 42.6% (2017), 49.1% (2018), and only 14.3% in 2019. The dominant races in 2019 were SGB (51.7%) and TGN (19.6%). One new race (TJQ) of P. graminis f. sp. avenae was detected in 2016 at one location near Emerson, Manitoba, which may have arisen from a single-step mutation to avirulence to Pg15 from race TJS.